Comparative efficacy of buparvaquone and imidocarb in inhibiting the in vitro growth of Babesia bovis - Cardillo, Natalia M.; Lacy, Paul A.; Villarino, Nicolas F.; Doggett, J. Stone; Riscoe, Michael K.; Bastos, Reginaldo G.; Laughery, Jacob M.; Ueti, Massaro W.; Suarez, Carlos E. (Frontiers in Pharmacology, 2024)
Introduction: Babesia bovis is an apicomplexan parasite responsible for bovine babesiosis, a tick-borne disease with a worldwide impact. The disease remains inefficiently controlled, and few effective drugs, including imidocarb dipropionate (ID), are currently available in endemic areas. The objective of this study was to evaluate whether buparvaquone (BPQ), a drug currently used to treat cattle infected with the Babesia-related Theileria spp. parasites, could be active against Babesia parasites. Herein, we compared the effect of ID and BPQ on B. bovis growth in vitro erythrocyte culture.We compared the effect of ID and BPQ on the culture-adapted Texas T2Bo strain of B. bovis. In vitro cultured parasites were incubated with ID and BPQ at two starting parasitemia levels (PPE), 0.2 % and 1%. In vitro cultured parasites were treated with ID or BPQ at concentrations ranging from 10 to 300 nM, during 4 consecutive days. Parasitemia levels were daily evaluated using microscopic examination. Data was compared using the independent Student's t-test.Results and Discussion: Both ID and BPQ significantly inhibited (p<0.05) the growth of B. bovis, regardless of the initial parasitemia used. At 1% parasitemia, BPQ had lower calculated inhibitory concentration 50 (IC50: 50.01) values than ID (IC50: 117.3). No parasites were found in wells with 0.2% starting parasitemia, treated previously with 50 nM of BPQ or ID, after two days of culture without drugs. At 1% parasitemia, no parasite survival was detected at 150 nM of BPQ or 300 nM of ID, suggesting that both drugs acted as babesiacidals.Conclusions: Overall, the data suggests that BPQ is effective against B. bovis and shows a residual effect that seems superior to ID, which is currently the first-line drug for treating bovine babesiosis globally.